Palm olein emulsion formation using crude extract of syzygium aromaticum as emulsifier - Ahmad, Kausar; Mohd Hassan, Norazian; Bakhtiar, M. Taher; Hadi, Janan Nima (2011)
One of the most commonly used dosage form in drug delivery systems is emulsion. It is useful for the delivery of drugs with poor water solubility, which do not formulate well in aqueous solutions. An emulsion is a dispersed system containing at least two immiscible liquid phases, typically a lipid phase and an aqueous phase. Emulsions may be either oil-in-water (o/w) or water-in-oil (w/o) emulsions. In the oil-in-water emulsion, oil droplets of the lipid phase are dispersed throughout the aqueous phase, while in water-in-oil emulsion, the aqueous phase is dispersed as droplets throughout the lipid phase. In addition, multiple emulsions such as oil-in-water-in-oil or water-in-oil-in-water emulsions can be prepared. The objective of this research is to determine the emulsion formation using various crude extracts of Syzygium aromaticum, commonly known as clove. The extracts were obtained by macerating in four types of solvents and followed by drying. The palm olein-water interfacial tension containing extracts from water and ethanol/water (1:1) decreased to 21-22 mN/m. Palm olein-in-water emulsions were prepared by homogenizing palm olein and distilled water in the presence of 10% crude extracts at 11,500 rpm for 20 minutes at 24 ±1°C. Tween® 20 was used as control. The extent of phase separation and changes in particle size distribution were monitored. The most stable emulsions can be obtained using the aqueous and ethanol/aqueous extracts (1:1). There was no phase separation and no significant change in the particle size within six months. Emulsion stability was poor when extracts from isopropanol/chloroform or ethanol/water (9:1) were used.